Efforts of MV. Vantage Crew in Preparation for PSC Inspection by USCG at Port Everglades Miami, USA - Kesuma, Oktaprianto Setya; Malik, Djamaludin; Anggraeny, Elva Febriana (Universitas Hang Tuah, 2025)
This study examines the readiness of the crew aboard MV Vantage in preparing for Port State Control (PSC) inspections conducted by the United States Coast Guard (USCG) at Port Everglades, Miami, USA, with a focus on the maintenance and operation of safety equipment. Using a qualitative approach with a descriptive method, data was collected through interviews, direct observation during safety drills, and document analysis, which was then processed using thematic analysis. The findings indicate that crew readiness is highly dependent on effective supervision of training and a deep understanding of safety equipment operational procedures, with challenges such as limited training time and a lack of discipline among crew members. This study highlights the need for synergy between safety equipment maintenance and human factors to enhance maritime safety and provides recommendations for improving ship safety standards.